Added value of multi‐pathogen probe‐based real‐time PCR SeptiFast in the rapid diagnosis of bloodstream infections in patients with bacteraemia. Issue 7 (July 2015) - Mongelli, Gino; Romeo, Maria Antonietta; Denaro, Carmelo; Gennaro, Mauro; Fraggetta, Filippo; Stefani, Stefania
Abstract : N/A: The commercial multi‐pathogen probe‐based real‐time PCR SeptiFast (SF) was evaluated as a rapid and complementing tool for the microbiological diagnosis of bloodstream infections (BSIs) in a series of 138 matched blood samples from 65 patients with bacteraemia, hospitalized in an intensive care unit, when antibiotics had already been administered. SF was positive in 32.6 % of the samples, whereas blood culture (BC) was positive in 21.7 % ( P < 0.05). SF identified more pathogens (11 versus 5; specificity, 90.7 %) and reduced the time of aetiological diagnosis, with a mean of 16.3 versus 55.4 h needed for BC ( P < 0.05). SF enabled appropriate pathogen‐oriented therapy in 72 % (36/50) of the BSI group of patients on the basis of epidemiological data. According to our data, the use of SF provided important added value to BC, in terms of earlier aetiological diagnosis of BSIs, enabling pathogen‐oriented therapy in patients receiving empirical antibiotic treatment.